Cost of Illness Study of Regular Out Patient Department Diabetic in a Low Income Country: A Cross Sectional Study - Kattel, V.; Subedi, M.; Agrawal, Y.; Pall, Z.S.; Rani, S.; Upadhyaya, S.; Lavaju, P.; Sarraf, D.K.; Maskey, R. (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Background: The burden of Diabetes in South Asia is alarming as the prevalence is higher compared to other region, living cost is low after Sub Saharan Africa and health care system are in state of expanding to be more accessible and adequate. Objectives: The objective of the study was to assess the direct cost of illness among diabetic patient regularly visiting at outpatient department (OPD) in BPKIHS. Methods: This was a cross sectional study done in year 2018. 142 patients with at least nine visit per year were enrolled. The direct cost were calculated from the pattern of prescription of medications and laboratory investigations carried out over a year of the individual patient. The data were tabulated and analyzed. Results: Among the 142 patients on 37.5% were in mono-therapy and 62.5% were in poly-therapy. The direct cost of illness was USD 103 per annum that includes drug and investigation cost expensed at OPD visit. The average indirect cost was USD 102 per annum including travel and food. Among 142 patient the cost of illness on inpatient due to DM was USD 85.47 per event. Conclusion: The financial burden of being a diabetic in Nepal is high. Comprehensive quality care by expansion of health system and service with nominal charges to patient seems to be one of the challenges in Nepal.